Influence of Respiratory Tract Infections on Vocabulary Growth in Relation to Child's Sex: The STEPS Study - Nylund Annette; Toivonen Laura; Korpilahti Pirjo; Kaljonen Anne; Åhlander Viveka Lyberg; Peltola Ville; Rautakoski Pirkko (MDPI, 2023)
Common health issues have been less examined in studies of early language development, particularly in relation to the child's sex. Respiratory tract infections, often complicated by acute otitis media, are common in children during the first years of life, when early vocabulary development takes place. The present study, conducted in Finland, aimed to investigate whether possible associations between recurrent respiratory tract infections, background factors, and vocabulary growth differ in boys and girls aged 13 to 24 months. The participants (N = 462, 248 boys and 214 girls) were followed for respiratory tract infections and acute otitis media from 0 to 23 months of age. The parents completed daily symptom diaries of respiratory symptoms, physician visits, and diagnoses. The expressive vocabulary was measured with parental reports. We found that recurrent respiratory tract infections were not associated with slower vocabulary development in boys or girls. In fact, boys with recurrent respiratory tract infections had more vocabulary growth during the second year than boys who were less sick. We found that vocabulary growth was associated differently with respiratory tract infections and background factors as a function of the child's sex. The vocabulary growth of boys seems to be more influenced by environmental factors than that of girls.